A drought-sensitive barley variety displays oxidative stress and strongly increased contents in low-molecular weight antioxidant compounds during water deficit compared to a tolerant variety - Marok, Mohamed Amine (Journal of plant physiology, 2013)
Copyright © 2013 Elsevier GmbH. All rights reserved.